Efficient water soluble nanostructured ZnO grafted O-carboxymethyl chitosan/curcumin-nanocomposite for cancer therapy. Issue 4 (April 2015) - Upadhyaya, Laxmi; Singh, Jay; Agarwal, Vishnu; Pandey, A.C.; Verma, Shiv P.; Das, Parimal; Tewari, R.P.
Graphical abstract Ex situ prepared novel highly soluble nanomatrix Cr/O-CMCS/n-ZnO NCs which have been used for preferential drug loading. The Cr/O-CMCS/n-ZnO NCs shows higher toxicity and cellular internalization within cancer cells (MA104 cell line) as compared to normal cells (L929 cell line) investigated via MTT assay and FACS analysis.